C-H Functionalization and C-N Bond Formation Approaches under Catalytic Conditions for the Synthesis of α-Ketoamides and 2,4-Disubstituted-1,3,5-triazines - Sidartha Singh, Laimujam; K. Kabi, Arup; Sengupta, Ragini; Roy, Anupam; Sahoo, Abhishek; Saha, Indranil; C. Malakar, Chandi (Asian Journal of Chemistry, 2022)
This work describes an easy way to perform approach for the transformation of arylmethyl ketones to α-ketoamides using secondary amines as starting materials in the presence of iodine as a catalyst in water under peroxide free reaction conditions. The established amidation reaction proceeds via α-C(sp3)-H functionalization and C-N bond formation approaches in water at ambient temperature. On the other hand, a novel and straightforward synthesis of 2,4-disubstituted-1,3,5-triazines via nickel-catalyzed cyclization of amidines with DMSO as one-carbon synthon has been developed. The developed strategy proceeds via C-N bond formation.